TOXIC EFFECTS OF SCORPION, HEMISCORPIUS LEPTURUS (HEMISCORPIIDAE) VENOM ON MICE - R. Dehghani; T. Khamehchian; B. Vazirianzadeh H. Vatandoost; S. A. Moravvej (Journal of Animal and Plant Sciences, 2012)
Scorpion stings are common in Iran, particularly in the southern and southwest regions of the country, and they pose a serious health problem. Hemiscorpius lepturus is the most venomous scorpion in the region. The present study was conducted to investigate the in vivo effects of scorpion venom in experimental mice. Haematological parameters (white and red blood cells numbers and haematocrit levels) and histological changes (skin, stomach, spleen, heart, liver, kidney, lung, pancreas, small intestine, anal, adrenal, brain, and bladder) venom were measured in mice. The results revealed that H. lepturus species has negative effects on both local and systemic tissues in mice, which may include damage to the skin and internal organs, respectively.
Keywords: Hemiscorpius lepturus; venom; mice; in vivo; haematological studies; histological studies